Autophagy in pulmonary macrophages mediates lung inflammatory injury via NLRP3 inflammasome activation during mechanical ventilation - Zhang, Yang (American Physiological Society, 2014)
The inflammatory response is a primary mechanism in the pathogenesis of ventilator-induced lung injury. Autophagy is an essential, homeostatic process by which cells break down their own components. We explored the role of autophagy in the mechanisms of mechanical ventilation-induced lung inflammatory injury. Mice were subjected to low (7 ml/kg) or high (28 ml/kg) tidal volume ventilation for 2 h. Bone marrow-derived macrophages transfected with a scrambled or autophagy-related protein 5 small interfering RNA were administered to alveolar macrophage-depleted mice via a jugular venous cannula 30 min before the start of the ventilation protocol. In some experiments, mice were ventilated in the absence and presence of autophagy inhibitors 3-methyladenine (15 mg/kg ip) or trichostatin A (1 mg/kg ip). Mechanical ventilation with a high tidal volume caused rapid (within minutes) activation of autophagy in the lung. Conventional transmission electron microscopic examination of lung sections showed that mechanical ventilation-induced autophagy activation mainly occurred in lung macrophages. Autophagy activation in the lungs during mechanical ventilation was dramatically attenuated in alveolar macrophage-depleted mice. Selective silencing of autophagy-related protein 5 in lung macrophages abolished mechanical ventilation-induced nucleotide-binding oligomerization domain-like receptor containing pyrin domain 3 (NLRP3) inflammasome activation and lung inflammatory injury. Pharmacological inhibition of autophagy also significantly attenuated the inflammatory responses caused by lung hyperinflation. The activation of autophagy in macrophages mediates early lung inflammation during mechanical ventilation via NLRP3 inflammasome signaling. Inhibition of autophagy activation in lung macrophages may therefore provide a novel and promising strategy for the prevention and treatment of ventilator-induced lung injury.